2021
DOI: 10.3390/ijerph19010300
|View full text |Cite
|
Sign up to set email alerts
|

‘A Safe Place Where I Am Welcome to Unwind When I Choose to’—Experiences of Brief Admission by Self-Referral for Adolescents Who Self-Harm at Risk for Suicide: A Qualitative Study

Abstract: Evidence is lacking on how to manage imminent suicidality in adolescents with self-harm. Brief Admission by Self-referral (BA) is a crisis-management intervention, developed for adults with self-harm at risk for suicide. Structured, individualized and based on responsible autonomy, BA aims to provide a respite while minimizing negative effects of hospitalization. This qualitative interview study illuminates adolescents’ experiences of BA, adapted for this target group. Nineteen adolescents aged 14 to 19 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…In order for staff to facilitate agency and recovery among adolescents, it was considered important to adapt PIBA from the adult setting and thus make adjustments to the youth context [cf. ( 13 )] that includes parents. Part of the recovery research on young people is about how care can be optimized and developed to best facilitate a recovery-oriented approach ( 33 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order for staff to facilitate agency and recovery among adolescents, it was considered important to adapt PIBA from the adult setting and thus make adjustments to the youth context [cf. ( 13 )] that includes parents. Part of the recovery research on young people is about how care can be optimized and developed to best facilitate a recovery-oriented approach ( 33 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through this (tentative) approach, we suggest that there is an explicit idea that PIBA may promote recovery and epistemic justice also for young people since they, to a greater degree, have the possibility to define and voice their needs rather than others defining and voicing these for them [cf. ( 12 , 13 )]. Providing PIBA to certain adolescents in CAP may change traditional structures of power and knowledge legitimacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender profiles of participants were reported in 25 studies. While one study included only female participants (Lindkvist et al, 2021) and one included only male participants (Hassett & Isbister, 2017), all other studies included a mix of female and male participants, with four studies including transgender, non-binary or other genders. Only three studies reported on participants' ethnicity, all of which included exclusively or majority White participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, others felt that they could call on staff freely within brief admission wards and also a sense of predictability and safety, unlike in busy and intense EDs (Lindkvist et al, 2021).…”
Section: Access To Carementioning
confidence: 99%